(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Emergency delirium (ED) is a common and distressing complication in children recovering from anesthesia, particularly after tonsillectomy. Dexmedetomidine, a selective α2-adrenergic agonist, has been investigated for its sedative and analgesic properties, potentially reducing the incidence of ED. However, its effectiveness in pediatric tonsillectomy patients remains an area of ongoing research. Aim: This study aimed to evaluate the efficacy of dexmedetomidine in reducing emergency delirium in children undergoing tonsillectomy. Methods: This prospective, randomized controlled trial was conducted at CMH Muzaffarabad, AJK Hospital, from October 2023 to September 2024. A total of 50 pediatric patients scheduled for elective tonsillectomy were enrolled and randomly assigned into two groups: the dexmedetomidine group (n=25) and the control group (n=25). The dexmedetomidine group received an intravenous infusion of dexmedetomidine (0.5 µg/kg) over 10 minutes before the end of surgery, while the control group received an equivalent volume of saline. The primary outcome was the incidence and severity of ED, assessed using the Pediatric Anesthesia Emergence Delirium (PAED) scale. Secondary outcomes included hemodynamic stability, postoperative pain scores, and recovery characteristics. Results: The incidence of ED was significantly lower in the dexmedetomidine group (16%, 4/25) compared to the control group (56%, 14/25) (p=0.003). The mean PAED score in the dexmedetomidine group was 6.8 ± 2.4, whereas it was 12.5 ± 3.2 in the control group (p<0.001). Postoperative pain scores were also lower in the dexmedetomidine group (3.1 ± 1.2 vs. 5.6 ± 1.8, p=0.002). No significant differences in hemodynamic parameters or recovery time were observed between the two groups. Conclusion: Dexmedetomidine significantly compact occurrence and severity of emergency delirium in pediatric patients experiencing tonsillectomy without causing notable adverse hemodynamic effects. Its use as an adjunct in pediatric anesthesia could improve postoperative recovery and patient comfort.